Professional Development, Motivation, and Job Satisfaction among Madrasah Tsanawiyah Teachers: Integrating Self-Determination Theory and Islamic Teacher Professionalism - Badrun Badrun (Jurnal Pendidikan Islam, 2026)
Teacher professional development, motivation, and job satisfaction are important factors that influence educational quality and teacher well-being, yet their interconnected relationships in madrasah contexts remain underexplored. This study aims to examine the direct and indirect relationships among professional development, work motivation, and job satisfaction among Madrasah Tsanawiyah (MTs) teachers in Nusa Tenggara Barat, Indonesia, using an integrated framework combining Self-Determination Theory and Islamic teacher professionalism. Employing a quantitative correlational design, data were collected from 345 teachers selected through stratified random sampling from public and private madrasahs. The data were analyzed using covariance-based structural equation modelling (SEM). The findings reveal that professional development positively influences both intrinsic and extrinsic motivation as well as teachers’ job satisfaction. Intrinsic motivation emerged as the strongest predictor of job satisfaction and significantly mediated the relationship between professional development and job satisfaction. These findings indicate that teachers’ professional satisfaction in madrasah settings is shaped not only by professional competence but also by meaningful engagement and value-oriented professional commitment. The study implies that professional development programs in Islamic education should prioritize autonomy, collaboration, reflective practice, and moral-professional engagement to strengthen teacher motivation, well-being, and sustainable professional commitment.